Pharmacological treatment optimisation for stable COPD: an endless story?: Proposals from the Société de Pneumologie de Langue Française. Issue 4 (12th October 2017) - Zysman, Maeva; Chabot, François; Housset, Bruno; Morelot Panzini, Capucine; Devillier, Philippe; Roche, Nicolas
In recent years, several global and local guidelines, recommendations and proposals on chronic obstructive pulmonary disease (COPD) management have been published [1–14]. They illustrate the great interest in this disease that, although no cure exists, is no longer considered untreatable. They also reflect its major and growing burden from both public health and individual perspectives. Finally, they parallel the increasing knowledge of its pathophysiology, clinical characteristics and natural history, as well as of treatment effects, with the goal of personalising care as much as possible. Here, we aim to present recent proposals of the French-Language Respiratory Society (Société de Pneumologie de Langue Française (SPLF)) and put them in perspective with the similarly recent Global Initiative for Chronic Obstructive Lung Disease (GOLD) document, which represents a major revision of GOLD proposals. It is also crucial to take this opportunity to emphasise here that the story of a guideline does not end with its production: the implementation phase is even more important and truly never ends until the next guideline, resulting in an endless cycle. Local adaptations of global recommendations on COPD may be necessary to facilitate appropriation and implementation http://ow.ly/wgNE30eONaG